Intenção de uso nas mídias sociais para o setor de serviços médicos e odontológicos: análise dos mecanismos e das condicionantes - Assis, Walter Macêdo de (2023)
The increasing growth of marketing in digital environments has changed market dynamics, which influences how consumers interact with brands and with each other. Through social media, the value co-creation between customer and company becomes increasingly important to the process of consumer engagement with the brand and the development of brand equity. The value co-creation process emerges as an important factor for professional service providers, who face a changing market environment, with increased competition and more technically savvy customers. Thus, the purpose of this work is to evaluate the effect of marketing communications on social media on consumers' intention to use medical and dental services. Value co-creation, brand equity, and engagement are mediators of the relationship. Additionally, the frequency of consumption is considered as a moderator variable. Data collection was carried out through a survey with social media users, and 376 valid responses were obtained. The proposed model was analyzed using the structural equation modeling technique, with the help of the SmartPLS 4 statistical software. . The results of this study confirm that: (1) value co-creation and engagement have a mediating effect on the relationship between social media marketing and purchase intention; (2) value co-creation and brand equity have a mediating effect on the relationship between social media marketing and purchase intention; (3) consumption frequency has a moderating effect on the relationship between value co-creation and brand equity. Value co-creation as an underlying mechanism between social media marketing and purchase intention has received little attention from academics. The empirical evidence of the antecedent relationship between value co-creation and purchase intention mediated by the constructs of brand equity and engagement presents relevant original contributions. As a practical contribution, the results of this research will allow the development of social media marketing strategies for the market of medical and dental services.